Longitudinal study of self-awakening and sleep/wake habits in adolescents - Ikeda H (Dove Medical Press, 2012)
Hiroki Ikeda,1 Mitsuo Hayashi21Department of Adult Mental Health, National Institute of Mental Health, National Center of Neurology and Psychiatry, Tokyo; 2Department of Behavioral Sciences, Graduate School of Integrated Arts and Sciences, Hiroshima University, Hiroshima, JapanAbstract: Self-awakening is the ability to awaken without external assistance at a predetermined time. Cross-sectional studies reported that people who self-awaken have sleep/wake habits different from those of people who use external means to wake from sleep. However, no longitudinal study has examined self-awakening. The present study investigated self-awakening, both habitual and inconsistent, compared to awakening by external means in relation to sleep/wake schedules for five consecutive years in 362 students (starting at mean age 15.1 ± 0.3 years). Students who self-awakened consistently for five consecutive years (5% of all students) went to bed earlier than those who inconsistently self-awakened (mixed group, 40%) or consistently used forced awakening by external means (56%). Awakening during sleep was more frequent and sleep was lighter in the consistently self-awakened group than in the mixed and consistently forced-awakened groups. However, daytime dozing was less frequent and comfort immediately after awakening was greater for the consistently self-awakened group than for the mixed and consistently forced-awakened groups. These results indicate that the three groups have different sleep/wake habits. Previous studies of self-awakening using cross-sectional survey data may have confounded both consistent and inconsistent self-awakening habits. A longitudinal study is necessary to clarify the relationship between the self-awakening habit and sleep/wake patterns.Keywords: habitual self-awakening, sleep/wake pattern, adolescent